Failure Behavior in Mechanical Testing of Two Plywood Products Distributed in Korea - In-Hwan Lee; Min Lee; Eun-Chang Kang; Yonggun Park; Sang-Min Lee (BioResources)
The structural performance was tested for two plywood products distributed in South Korea: Plywood for roof (RP) and plywood for concrete form (CP), in accordance with ASTM standards. The evaluation included tests for tensile-shear strength under wet conditions, bending performance, compressive strength, and rolling shear strength. Results indicated that the CP specimens exhibited a compressive strength of 37 MPa, surpassing that of structural cross-laminated timber (CLT) with comparable specific gravity. The bending performance of CP plywood was also notable, with a modulus of rupture of 56.8 MPa and a modulus of elasticity of 12 GPa. The rolling shear strength was measured at 2.4 MPa, which is favorable compared to the rolling shear strengths of European structural wood species. Notably, the failure pattern was ideal. Furthermore, the CP specimens demonstrated excellent adhesive strength in the tensile-shear test after cyclic boiling, both meeting and exceeding the Korean standards for structural plywood in all evaluated aspects. In contrast, the RP specimens did not fully meet some of the Korean standards, indicating areas for improvement in structural applications.